THE ROLE OF THE PUBLIC SECTOR IN CORPORATE SOCIALRESPONSIBILITY DEVELOPMENT IN LITHUANIA - Štreimikienė, Dalia; Pušinaitė, Rasa (Ekonomika, 2009)
In implementing sustainable development policy, corporate social responsibility and other voluntary business initiatives plays the crucial role. Business plays the central role in economy and its voluntary initiatives such as signing the Global Compact and developing corporate social responsibility (CSR) are the main tools for implementing sustainable development on local, regional and global levels. However, also the public sector plays an important role in enhancing CSR development in the country. There exit several studies on CSR development in the Lithuanian private sector; however, the role of the public sector has not yet been investigated.The aim of the work was to investigate the development of CSR in the Lithuanian public sector. The main goals of the article are to analyse the concept of corporate social responsibility and to identify the main driving forces of CSR development in the public sector, its main barriers and means of overcoming these barriers.The article summarizes the results of a survey conducted in the Lithuanian public sector. The survey has shown that corporate social responsibility is not widely spread among public administration bodies at the local level. The main factors having a negative impact on social responsibility development in the public sector are the lack of information, of human and other resources.